Comparative analysis of slope classes and terrain ruggedness index using distinct digital elevation models in the Municipality of Jenipapo de Minas (International Journal of Geoscience, Engineering and Technology, 2024)
This study assesses terrain variability in the Municipality of Jenipapo de Minas, southeastern Brazil, using Digital Elevation Models (DEMs). The DEMs analyzed include the Shuttle Radar Topography Mission (SRTM) with 30-meter (SRTM30) and 90-meter (SRTM90) resolutions, as well as the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER). The comparative analysis was based on topographic characteristics, such as slope and terrain ruggedness index (TRI) were derived from these models to analyze the landscape’s elevation changes. Results showed that elevation differences among the DEMs were similar. The predominant slope was undulating and heavily undulating, consistent with previous studies. The TRI results indicated a high incidence of level terrain, particularly in SRTM30 with 100% of the area and ASTER with almost 100%. However, in the SRTM90, the incidence of the nearly level and slightly Rugged TRI classes in 6.88% of the study area. These findings emphasize how DEM resolution influences terrain characterization, with implications for hydrological studies, environmental planning, and landscape management. Overall, the study underscores the necessity of carefully selecting DEM sources according to the specific analytical requirements, as well as the potential for using a combination of DEMs for a more comprehensive understanding of terrain dynamics across different spatial scales.